Business Opportunities in Industrial Revolution 4.0 through 9 (nine) E-commerce Marketing Strategies - Wahyu Sardjono; Winda Dian Nuriana (Bina Nusantara University, 2020)
Technological developments in industry 4.0 which lead to digital technology create new ideas for companies to take strategic steps in business processes. One of them is utilizing electronic commerce. This study uses a qualitative analysis approach which uses secondary data. The methodology used is conceptual review by gathering data and information that are interrelated. The information collected is market opportunity, consumer behavior and electronic commerce technology as an innovation in marketing. This research is expected to create potential market opportunities. The marketing strategy used is the strategy of utilizing technology, market opportunities, marketing strategies, designing consumer knowledge, creating consumer interfaces, increasing customer information creating marketing programs, and evaluating marketing programs using technology and information and program evaluation.